The Influence of Brand Image and Price on Purchasing Decisions: Study On One of The Red Ginger Companies in Bandung - Guruh Dwi Putra; Iwan Sidharta; Jimmy Rusjiana; Kadir Kadir (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study examines the impact of brand image and pricing on consumer purchasing decisions at a red ginger company in Bandung. This study examines the predominant aspects affecting purchasing decisions: brand image and price. The research methodology employed is route analysis, utilizing a sampling procedure via a questionnaire administered to one hundred consumers who exclusively utilize red ginger goods from the examined company. The study's findings demonstrate that brand image directly affects purchase decisions and indirectly influences them via the price variable. Similarly, price directly affects purchasing decisions and indirectly influences them via brand image. Examining the coefficient of determination demonstrates that brand image and price significantly influence purchasing decisions. However, other external factors beyond the analyzed variables also exert an impact that warrants consideration. In light of these findings, enterprises should prioritize enhancing brand image and adjusting competitive pricing to bolster customer purchasing decisions. Companies can enhance brand identity through effective marketing and uphold product quality to meet consumer expectations. Moreover, establishing pricing that aligns with the product's worth is crucial in sustaining consumer loyalty. This study's results are anticipated to guide corporate management in developing more effective marketing strategies to enhance competitiveness in the red ginger industry.